1999
DOI: 10.1177/108835769901400204
|View full text |Cite
|
Sign up to set email alerts
|

Respite Care Needs of Parents of Children with Developmental Disabilities

Abstract: The purpose of this study was to identify the respite care needs, and the impact of a lack of respite care, among families of children with developmental disabilities. A respite care needs assessment survey was completed by 574 lowan families of children with developmental disabilities. The results documented a void in the availability and accessibility of respite services regardless of demography, income level, or extent of disability. Respondents generally perceived that the availability of respite care serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 13 publications
0
20
0
1
Order By: Relevance
“…Families with children with disability were found to have troubles such as psychological and economical issues, future concerns, anxiety about child's possible accident or injury, breaking up the relationships between family and social environment, difficulty in treatment and education period, neglecting the other children, disappointment, feeling of guilt, communication with other members of the family and problems in sexual life [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Families with children with disability were found to have troubles such as psychological and economical issues, future concerns, anxiety about child's possible accident or injury, breaking up the relationships between family and social environment, difficulty in treatment and education period, neglecting the other children, disappointment, feeling of guilt, communication with other members of the family and problems in sexual life [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the study carried out by Yavuz and Çimen, 14 children with cerebral palsy are lacking in self care in areas including sleep-restinghaving fun, cleaning, oral care, toilet and eating. Abelson 15 determined that families need help related with issues such as preparing the food for the children, giving medications, bathing, oral care, feeding, putting on diapers, going to toilet, putting on clothes, protecting the child from danger and self-injuries inflicted by the children. The results of our study are in accordance with this literature.…”
Section: Discussionmentioning
confidence: 99%
“…A meeting at CYCD was carried out during January [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]2012 to present information about the study to the parents, to receive written and verbal consents and to enable them to meet with the researcher following the determination of the addresses of the disabled children registered in the home care service of CYCD. All home visits were made by a single researcher.…”
Section: Interventionmentioning
confidence: 99%
“…Though the impact of services on children has received little scrutiny (Gerard, 1990;Preece, 2002), research has identified their positive impact upon parents of children with ASD. Stress levels are reduced in the majority of families where short breaks services are available (Chan & Sigafoos, 2001;Factor, Perry, & Freeman, 1990;Gray, 1994) and it is generally acknowledged that appropriate short breaks can help prevent family breakdown (Abelson, 1999;Boyd, 2002). The literature is too extensive to review fully in a paper of this length; however, Sigafoos (2000, 2001) comprehensively review research undertaken in this field.…”
mentioning
confidence: 95%